The effect of using some teaching aids as delayed feedback on learning free style- back stroke- Brest stroke swimming - Adel, Omar (Journal of Physical Education, 2013)
This study aims to provide the influence of delayed feedback by using some teaching aids like : showing a model by video – showing a video taped performance of a student and copying a model all of ( free style- back stroke- Brest stroke ) . The second objective of the study is to know the differences between the experimental group and the control group with regard to the level and skill(Technique – time – average speed ) in these types of swimming styles . The experimental method has been adopted for this study because it is suitable for it . A random sample of 20 students who have taken the courses of swimming ( free style - back stroke - Brest stroke in the faculty of physical Education at Baghdad university in the year 2012-2013 were the subjects of this study . The students were divided into 2 groups : 10 in the experiment and 10 in the control the technological method ( using modern teaching aides such as video and video camera – copying model ) was used , while the traditional way of teaching(verbal-copying model )was used ( with the control group ) . The result of the study showed that there are significant differences between the measures of the levels of the experimental group in pre and post measurements in terms of technique- time and average speed ,for the benefit of experimental group . They also showed a difference in the level of skill between the two groups. the researcher recommends using new technological methods and Similar studies to smaller ages as well as in different sport activities .